Long-term follow-up of school-age children on the effectiveness of myopia correction with contact lenses - Nataliia Aleieva; Sergiy Rykov; Iryna Shargorodska; Mykola Petrovsky (Kazimierz Wielki University, 2021)
Introduction and purpose. Early use of contact correction for congenital myopia and astigmatism in children and adolescents contributes to their social rehabilitation. The myopia correction with contact lenses provides sustainability of correction and absence of periods of blurred retinal images, which are experienced with the use of glasses. The purpose of the study was to determine, through long-term follow-up, the extent to which contact lens correction improves uncorrected and maximally corrected visual acuity in school-age children with myopia and myopic astigmatism. Material and methods. We followed up for three years 84 children (168 eyes) aged 6-16 years with myopic manifest refraction and astigmatism, who used soft silicone hydrogel aspherical contact lenses to correct ametropia. In the early and late follow-up, these patients were examined for visual acuity, objective and subjective clinical refraction, axial eye length, corneal thickness and diameter, keratometry, and phorometric data (accommodation, vergence, disparate areas, and oculomotor apparatus and their interaction). Results.In course of long-term monitoring of myopia and myopic astigmatism correction with contact lenses in school-age children, the statistically significant results were recorded after three years of observation, namely: an increase in uncorrected visual acuity by 47% (t=5.2; p<0.01), corrected acuity vision by 8% (t=9.3; p<0.01), the spheroequivalent by 17% (t=3.7; p<0.01), anteroposterior segment of the eye by 4% (t=7,1; p<0.01), amplitude of accommodation by 27% (t=14.6; p<0.01), negative part of relative accommodation by 17% (t=7.3; p<0.01), positive part of relative accommodation by 32% (t=7.1; p<0.01), flexibility of accommodation by 35% (t=14.2; p<0.01), the ratio of accommodation convergence to accommodation by 19% (t=3.4, p<0.01), stereovision acuity by 56% (t=4.1; p<0.01), as well as a decrease in keratometry index in the strong meridian by 2% (t=5.2; p<0.01), delays in accommodative responses by 33% (t=14.2; p <0.01), distance phoria by 16% (t=10.1; p<0.01), near phoria by 16% (t=11.3, p<0.01). Conclusions. The study has shown that the use of contact lenses by school-aged children with myopia and myopic astigmatism can increase uncorrected and maximum corrected visual acuity. The increase of the spheroequivalent and anteroposterior axis (APA) of the eye indicates progression of myopia, but the use of soft contact lenses (SCL) leads to changes of the anterior corneal surface: an increase of the thickness in the central zone, and its flattening. Improvement of accommodation, vergence, disparate parts of the oculomotor apparatus, and their interaction was also observed. The results obtained indicate deceleration of myopia progression.